ROLE OF EXERCISES AND DIETARY INTAKE AS AN INTERVENTION IN WEIGHT REDUCTION (International Journal of Physiotherapy, 2016)
Background: Obesity is now so common within the world’s population that it is beginning to replace under nutrition and infectious disease as the most significant contributor to ill health. Exercise plays significance role with dietary control in weight reduction. The aim of our study is to find out the efficacy of weight reduction interventions and role of exercise.Methods: The study was conducted on 60 participants, subjects or participants were randomly divided. It is an experimental study which was completed in the duration of about six months. The study was based on two groups that are group A (exercise plus dietary) and group B (only dietary) consisting of sixty participants after filling the consent form.Result: Result shows out of these sixty only fifty eight participants completed the study and were observed for four months. Is has been found comparable weight loss relatively fewer in the dietary group Body weight before (80.1±2.7) after (78.1±2.5)and BMI before (32±2) after (30±2) it shows significant results but less significant than group A body weight which was before(78.6±2.6) after(64.0±2.3) and BMI before (33±1) after (39±1). Therefore the results shows that the group A shows more significant outcomes as compare to the other group included in the study.Conclusion: The results shows that (exercise plus dietary) more significant outcomes as compare to the other group included in the study